Modeling and Estimation of Physicochemical Properties of the Liquid Fuel Obtained from the Catalytic Pyrolysis of Disposable Masks (LACCEI, 2024)
The present research studies the modeling and estimating of the physicochemical properties of the liquid fuel obtained from the catalytic pyrolysis of disposable masks. The modeling and simulation of a liquid fuel stream obtained using the DWSIM Process Simulator (free software) was carried out, experimental results of the Distillation at 760 mmHg (ASTM D86) test were taken, and the simulator's distillation curve tool was used. Likewise, the Cold Flow properties estimation tool and the heating power estimation supplement were used to estimate the results. A comparison of the estimated results with the experimental results is performed, as well as a comparison of the results obtained with the technical specifications of Diesel B5 S-50. It is concluded that it is possible to model and simulate a liquid fuel stream obtained from disposable masks, and the estimation of the gross heating power and density properties of a liquid product stream of disposable masks are considered good estimates (error less than 5%). Likewise, it is concluded that the liquid product obtained from the pyrolysis of disposable masks is within the technical specifications of Diesel B5 S-50 for the analyzed parameters.